Perancangan Interior “Café Bikers” Di Surabaya - I Made Bagus; Sriti Mayang Sari; Linggajaya Suryanata (Intra, 2019)
The expansion of “Big Bike” in Surabaya has a significant development, supported by Surabaya as one of the cities with the fastest growth of “Big Bike” community. The “Big Bike” community has some variety of activities, from mere gatherings (“kopi darat” in bahasa) where each members of the “Big Bike” community will gather in a predetermined place, usually at a café that is sufficient to accommodate several motorbikes, because they will gather for quite a long time for chatting, using the café facilities, or even hold events such as a “show offs”, where the members that has motorbikes modifications join the event to show off their work. This statement leads to the need of providing the “Big Bike” community’s activities. Therefore, the design of the bikers café was aimed to fulfill their usual activities, that may not be found in other Surabaya cafés that answers the needs with easier technology. The concept is the “One Stop Service”, where the café provides a room for workshops, special rooms for motorbike maintenance (motorbike salons, services and also modifications), accompanied by the technology through gadgets or other technological facilities. This facilitates the Big Bike community because they do not need to move around to find needed facilities. The application of this concept is expected to be able to accommodate the needs of the Big Bike Community in Surabaya to make it easier to find a café that supports the community's activities.